Byggnadsutformning med avseende på en verksamhets arbetssätt : Applicerat på Räddningstjänstens nya stationsbyggnad i Kiruna - Rönnlund, Josefine (2014)
When designing new work places, an investigation about how the organization works is necessary. Many times the work place is designed with similar planning as the previous work place but with a newer building design. Instead, the patterns of movement of the company’s personnel should be examined to get a clear picture of how the people move inside the current builiding; what movement is good, what is bad and what should be transferred to the new design. There is also a risk that the common areas is designed after all the other company-specific activities. Thus the areas may be shoved away in places that leads to segregation amongst the personnel and less interaction as if the common areas were placed more integrated with the other activities.Kiruna Firedepartment face a relocation of its operation due to the fact that the mining company LKAB intend to expand their mining operations. Therefore the current building has to be demolished and a new fire station is to be built in a another place. The firedepartment also stands before changes in its operation and becaus of the move this is a perfect opportunity to evaluate how the personnel works, to design the new work place with the best conditions for the firedepartments way of work.The research is done with a theoretical base and from this a list was produced that showes factores which you should have in mind whilst designing work places. The firedepartment has been integrated in the design process through continuous meetings where the personnel got to express their oppinions about the design work and the final design. This thesis has examined the the movement patterns of the people in the firedepartment today with qualitative interviews and observations. This had to be done since the current building is no longer adapted to the current way of work in the fire station. This research is applied to three conseptual designes and finally one to show how new work places can be designed for a company with a complex way of work.So how can a building be designed based on ...